Optimizing students' writing development through electronic feedback via Microsoft Word - Mekah Syahfitri; Amrizal Amrizal; Nil Adrian Afandi Matondang; Rona Adani Ulayya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Students writing skills are a key component of language learning. Nevertheless, in practice, teachers provide little feedback, and many students struggle to improve their writing. Electronic feedback has evolved into a powerful method for facilitating students' writing growth in the digital age. The objective of this study is to investigate the use of electronic feedback via Microsoft Word to maximize students writing development. A qualitative descriptive research design was used, with participants comprising 15 fourth-semester undergraduate students. Data were collected through observation, documentation, and the analysis of students' written assignments. The findings indicate that feedback received electronically in Microsoft Word, such as through comments and track changes, assists students in recognizing errors in their writing (grammar and vocabulary) and revising it more effectively. In addition, this type of feedback boosts students' motivation and engagement with the writing process. Therefore, electronic feedback in Microsoft Word can be considered an effective strategy for supporting students writing development in English language learning.